An introduction to solution focused brief therapy with clients who stammer - Nicholas, Alison (Henry Stewart Talks, 2016)
Key underlying principles of SFBT, Typical structure of an SFBT session, How to identify best hopes from therapy & preferred future, Use of scaling questions to reflect on progress, Evidence base of SFBT, Benefits of using solution focused ideas